Elements of Euphemism in Malay Proverbs: An Inquisitive Semantic Analysis (Jurnal Bahasa, 2023)
Euphemism is an expression or word that is more soft, polite, and sweet to hear as an effort to replace a harsher expression or word. The observation of the Malay people on their surrounding environment allows them to create a representation based on objects that exist for the purposes of speaking and offering advice. Thus, this study was conducted to identify and analyze the conception of euphemism through the objects of humans, animals, and plants as well as to discover the implicit meaning behind a proverbial expression. A total of 15 proverbs (data) were successfully collected from Kamus Istimewa Peribahasa Melayu compiled by Abdullah Hussain and the website of Pusat Rujukan Sehenti Penyelidikan Alam Melayu by the Institute of the Malay World and Civilization (ATMA), Universiti Kebangsaan Malaysia (UKM). The Inquisitive Semantics approach and Bridging Cross Reference (BCR) subconcept as well as constructed image were implemented in this study to analyze the data collected. The findings indicate that the euphemistic proverbs that were used since the olden times are closely related with the Malay people's conduct and culture. The figure of speech used when communicating clearly reflects the sharp-mindedness and richness of the Malay language. An adequate semantic analysis couched in an appropriate approach is able to describe implicit meanings that reflect aspects of the Malay mind.Keywords: Malay proverb, euphemism, Malay philosophy, inquisitive semantics, bridging cross reference, metaphorFull text: PDF